1996
DOI: 10.1111/j.1432-1033.1996.0232h.x
|View full text |Cite
|
Sign up to set email alerts
|

Microperoxidase/H2O2‐Catalyzed Aromatic Hydroxylation Proceeds by a Cytochrome‐P‐450‐Type Oxygen‐Transfer Reaction Mechanism

Abstract: The mechanism of aromatic hydroxylation of aniline and phenol derivatives in a H,O,-driven microperoxidase-8(MP8)-catalyzed reaction was investigated. It was shown that the reaction was not inhibited by the addition of scavengers of superoxide anion or hydroxyl radicals, which demonstrates that the reaction mechanism differs from that of the aromatic hydroxylation catalyzed by a horseradish peroxidase/ dihydroxyfumarate system.Additional experiments with lXO-labelled H,'*O, demonstrated that the oxygen incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
78
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 29 publications
4
78
0
Order By: Relevance
“…Recent studies, however, have demonstrated that this approach needs further optimization [10]. Alternatively, modified hemoproteins such as microperoxidases might be used to catalyze hydroxylations by a P450-like oxygen transfer mechanism, but so far these catalysts do not exhibit the necessary performance and selectivity [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, however, have demonstrated that this approach needs further optimization [10]. Alternatively, modified hemoproteins such as microperoxidases might be used to catalyze hydroxylations by a P450-like oxygen transfer mechanism, but so far these catalysts do not exhibit the necessary performance and selectivity [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…After 1-min incubation, the reaction was terminated by cooling the samples on ice. The incubation time was taken as 1 min because of the catalytic instability of MP8 (6,9). This reaction mixture was then concentrated by evaporation to about 50 l (methanol incubations) or about 20 l (ethanol incubations).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, recent work has demonstrated that MP8, especially in the presence of ascorbic acid, could, like cytochromes P450, mediate oxygen transfer reactions from hydrogen peroxide to substrates (6,7). More recently, we showed that the MP8͞ H 2 O 2 system catalyzes the dehalogenation of para-halogenated phenols, resulting in the formation of p-benzoquinones as the primary and only dehalogenated products (19).…”
mentioning
confidence: 99%
“…Upon reac-450-type of mechanism involved in these conversions on the tion with H 2 O 2 MP-8 forms high-valency iron-oxo intermediates basis of the observation that (a) microperoxidases can use as that could be analogous to compounds I and II of horseradish oxygen donor either H 2O2 alone or a system consisting of O2, peroxidase [3], although the exact nature of these high-valency a NADPH-regenerating system and NADPH :cytochrome P-450 species was not unambiguously proved. Recently, Low et al [4] reductase which is inhibited by CO [7]; (b) radical scavengers showed that compound II of MP-8, produced by photochemical have no influence on the extent of the reaction with H 2 O 2 [8] oxidation, consists of the ferric cation-radical porphyrin form and the oxygen incorporated into the substrate is derived from and the ferryl form, interconverted pH-dependently by intramo-H 2…”
mentioning
confidence: 99%
“…Microperoxidase-8 (MP-8) is a heme-containing octapeptide chrome P-450-type conversions, such as the para-hydroxylation of aniline [7,8], the N-demethylation of tertiary amines and the obtained by proteolytic digestion of horse-heart cytochrome c S-oxygenation of methyl phenyl sulphide and phenacyl phenyl [1,2], containing Fe(III)-heme covalently attached to a residual sulphide [9]. Some of these studies reported on the actual Poctapeptide derived with histidine as the fifth ligand.…”
mentioning
confidence: 99%